Increasing Students’ Awareness in Speaking Participation - Muhammad, Ribeh Najib (Universitas Muhammadiyah Gresik, 2019)
The lack of students’ activities seems to be the main reasons why the teacher failed to maximize the participation of the students in a senior high school in a small city in East Java Indonesia. The unification of two different basic competences into one lesson plan also makes the indicator of the lesson plan become not too clear and not specific enough. Thus the research questions of this study are: 1. How is the implementation of the teaching and learning process based on the revised lesson plan conducted by the teacher? 2. How is the teaching and learning process based on the revised lesson plan followed by the students? 3. How is the students’ participation in learning speaking after the teaching and learning process based on the revised lesson plan conducted? This research is a classroom action research with one cycle only. The first data is in the form of description of the teacher’s activities during the teaching and learning process, the source of the data is the teacher who conducts the revised teaching-learning process. The second data is the description of students’ activities during the teaching and learning process, the source of the second data is the students who follow the teaching and learning process based on the revised lesson plan. The third data is the participation of the students when they are taught using the revised lesson plan, the third source of the data is also the students who follow the teaching and learning process based on the revised lesson plan. The researcher used unstructured field notes to write all the information which were seen and heard and also everything that happened during teaching and learning process conducted by the teacher. The data need to be sorted and classified to know the relevant data and non-relevant data. Then the relevant data were classified based on each research question to be analyzed. The students’ participation in the teaching and learning process of speaking narrative text based on the revised lesson plan was better, because the students could follow the instructions and do the activities of speaking narrative text smoothly, every student was able to present their stories in the group and in front of the class, they were active in the group discussion for asking and answering their friends’ question, they were also active in asking questions to the teacher and answering questions from the teacher.